Association of sleep hygiene knowledge and physical activity with sleep quality in nursing and medical students: a cross-sectional study - Saintila, Jacksaint; Javier-Aliaga, David; del Carmen Gálvez-Díaz, Norma; Barreto-Espinoza, Luz Antonia; Buenaño-Cervera, Noemi A.; Calizaya-Milla, Yaquelin E. (Frontiers in Sports and Active Living, 2025)
BackgroundSleep quality and physical activity are fundamental factors in the optimal functioning of the human organism and maintaining overall health. This study aimed to evaluate the relationship between knowledge of sleep hygiene and physical activity in relation to sleep quality among nursing and medical students.MethodsIn a cross-sectional online study, a suitable and convenient sample of 300 nursing and medical students from a private university located in Chiclayo, Peru, was collected. Data were collected using the following instruments: a questionnaire concerning sleep hygiene knowledge, the International Physical Activity Questionnaire (IPAQ), and the Pittsburgh Sleep Quality Index (PSQI). The data collection period spanned January and February 2024.ResultsOf the total sample, 59.3%, 51.7%, and 69.7% reported insufficient knowledge of sleep hygiene, low physical activity and poor sleep quality, respectively. Sleep hygiene knowledge and physical activity explained 17.9% of the variability in sleep quality (R2 = 0.179, F = 32.31, p < 0.001). In addition, there is a positive and significant association between knowledge of sleep hygiene (β = 0.27; p < 0.001) and physical activity (β = 0.24; p < .001) with sleep quality.ConclusionThe findings indicate that interventions designed to improve sleep hygiene knowledge and physical activity may be effective strategies for improving sleep duration among nursing and medical students.